Culture-based tourism development strategy in Tegalinggah Hamlet, Bedulu Village, Blahbatuh, Gianyar - Wulan, Anak Agung Istri Ratna Sari; Seniartha, I Wayan; Darmaputra, Putu Gede Eka; Putra, Dewa Gede; Launingtia, I Gusti Ayu Niken (School of Tourism, Universitas Ciputra Surabaya, 2024)
This study focuses on developing a culture-based tourism strategy for Tegalinggah Hamlet, Bali, to address challenges while leveraging local opportunities. A SWOT analysis reveals strengths such as archaeological heritage and man-made attractions, combined with accessible locations, and opportunities in the realms of spiritual tourism and the European market. However, drawbacks include management deficiencies, a lack of digital information, and ineffective promotional efforts. Additionally, threats arise from competing attractions, insufficient support, market fluctuations, and poor management practices. To counter these issues, the study proposes a multifaceted solution incorporating innovative digital marketing, strategic external partnerships, a robust online presence, effective management practices, and product differentiation. These initiatives aim to foster sustainable tourism, enhance local economies, and maintain environmental integrity in a competitive landscape. By implementing these strategies, Tegalinggah Hamlet can cultivate a distinctive tourism identity that not only attracts visitors but also supports the community and preserves cultural heritage for future generations. The findings contribute to a comprehensive approach to tourism development, balancing economic growth with cultural preservation in Bali.